2016
DOI: 10.1080/10495398.2016.1178140
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Growth and Reproduction Performance, Transgene Integration, Expression, and Transmission Patterns in Transgenic Pigs Produced by piggyBac Transposition-Mediated Gene Transfer

Abstract: Previously we successfully produced a group of EGFP-expressing founder transgenic pigs by a newly developed efficient and simple pig transgenesis method based on cytoplasmic injection of piggyBac plasmids. In this study, we investigated the growth and reproduction performance, and characterized the transgene insertion, transmission and expression patterns in transgenic pigs generated by piggyBac transposition. Results showed that transgene has no injurious effect on the growth and reproduction of transgenic pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…2). Previous studies have indicated that the transgene copy number is positively correlated with expression level in TG animals5051. Therefore, it may be possible to increase the production level of hNGF by generating TG animals with higher transgene copy numbers, for example by increasing the amount of plasmid DNA used during microinjection48.…”
Section: Discussionmentioning
confidence: 99%
“…2). Previous studies have indicated that the transgene copy number is positively correlated with expression level in TG animals5051. Therefore, it may be possible to increase the production level of hNGF by generating TG animals with higher transgene copy numbers, for example by increasing the amount of plasmid DNA used during microinjection48.…”
Section: Discussionmentioning
confidence: 99%